COVID-19 Generated Personal Protective Equipment: Sources of Microplastics and Pathogen Vectors in Marine Environments? - Noman, Md Abu; Sun, Jun; Hossain, Mohammad Belal (Frontiers in Marine Science, 2021)
The world has already experienced the severe adverse effects of COVID-19 at every level. When it became understood that the COVID-19 infection is spread in the community via respiratory transmission from humans, then the widespread use of plastic-made personal protective equipments (PPEs) like face masks and hand gloves tremendously increased throughout the world. Although it has reduced the spreading of virus, however, careless disposal or mismanagement of these single use PPEs has created another major concern for the environment, as plastics are a known source of environmental contamination. On one hand, they are infected with SARS-CoV-2, while on the other, they act as a carrier or vector or pathway for other pathogens or diseases, and hence can increase the degree of continuing the pandemic. Besides, there might be a chance that plastics or microplastics may be responsible for introducing new pathogenic viruses or bacteria to humankind. As such, it is clear that more research needs to be conducted to clarify this fact, and its underlying mechanisms. In this review, we briefly explored how PPE used in the COVID-19 pandemic aggravated existing microplastic pollution, how they could act as disease routes or vectors, and how they could introduce new pathogens to the terrestrial and marine environment. Addressing these questions may create awareness of plastic use, waste management, and enact relevant policy which may protect our environment and health.